Community Structure and Carbon Stock of Mangrove Sediments in Sembilang National Park Area - Muhammad Fadlurrohman Ash Raffi; Taryono Taryono; Ali Mashar (Jurnal Ilmu Pertanian Indonesia, 2026)
Increased greenhouse gas emissions have led to climate change. Indonesia plans to reduce greenhouse gas emissions by 140 million tons of CO₂-equivalent (CO₂e) by 2030. One strategy for achieving this goal is to conserve mangrove habitats. However, unsustainable activities continue to jeopardize the survival of these mangroves. The purpose of this study was to investigate the community structure and sediment carbon content of mangrove ecosystems in Sembilang National Park. Data was obtained at three stations using 100-m transects extending inland from the seashore or riverbank. The sediment carbon analysis was carried out utilizing the Loss on Ignition (LOI) method. Excoecaria agallocha had the highest Importance Value Index (IVI) at the Sungai Barong station, followed by Rhizophora apiculata in the Sungai Sanjang and Birik stations. The mangrove ecosystems at the study sites were characterized as moderately dense. The investigation revealed that the carbon store in mangrove sediments was 1294.14 t/ha, with an average of 431.38 t/ha. Mangrove ecosystems must be managed and protected to ensure that they continue to provide ecological and economic advantages. Keywords: carbon stock, climate change, mangrove